Internal Motivation of College Attendance for Instructional Design Course - Setiawan, David Firna (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2019)
Attendance is considered as a form of participation in learning. One way of participation that becomes a study among researchers is the presence of students in lectures. However, the difference regarding the motives for the existence of students in lectures is still a question. This study aims to explain the relationship between internal motivation towards student attendance in lessons. This knowledge is essential related to the strategies that can be carried out by the department of economic education to increase attendance to achieve specific academic goals. Furthermore, the strategy to increase attendance can be a preventive measure to anticipate or reduce student deviant behavior. The results showed that the proposed independent variables, namely, (1) enjoyment, (2) challenges, and (3) awareness, did not affect the presence of students in instructional design courses either partially or simultaneously so that in this study, these variables were not well used as a predictor of attendance. Therefore, the next study can propose variables, differences in student characteristics, and other methods to explain the motive for attendance.